2016
DOI: 10.1128/aem.00052-16
|View full text |Cite
|
Sign up to set email alerts
|

Metrics Proposed To Prevent the Harvest of Leafy Green Crops Exposed to Floodwater Contaminated with Escherichia coli

Abstract: , 2012). Further, previously flooded soils should not be replanted for 60 days. In this study, the suitability of the LGMA metrics for farms in the Mid-Atlantic region of the United States was evaluated. The upper end of a spinach bed (in Beltsville, MD) established on a ؊5% grade was flooded with water containing 6 log CFU/ml Escherichia coli to model a worst-case scenario of bacterial movement through soil. Escherichia coli prevalence in soil and on foliar tissue was determined by most probable number (MPN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other work evaluating the survival of a multistrain inoculum of nonpathogenic E. coli in soils flooded with diluted dairy manure runoff has shown that survival durations in a clay loam soil were longer in a fall season compared to spring season (38). In that study, slow die-off E. coli in manure-amended soils in the fall season compared to a spring season was attributed to lower temperatures and exposure to less UV (i.e., UV-B) radiation.…”
Section: Discussionmentioning
confidence: 76%
“…Other work evaluating the survival of a multistrain inoculum of nonpathogenic E. coli in soils flooded with diluted dairy manure runoff has shown that survival durations in a clay loam soil were longer in a fall season compared to spring season (38). In that study, slow die-off E. coli in manure-amended soils in the fall season compared to a spring season was attributed to lower temperatures and exposure to less UV (i.e., UV-B) radiation.…”
Section: Discussionmentioning
confidence: 76%
“…Although the Weibull model was used for E. coli O157:H7 survival in soil (11), we used the log-linear survival models for model simplification and an increase in computational efficiency. Log-linear survival models have been reported previously for survival of E. coli O157:H7 in soil (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…In turn, extreme weather events, such as flooding, were shown to increase the prevalence of Escherichia coli and Salmonella spp. [26,27]. In addition, rain splashing and storm water runoffs were also shown to facilitate the dispersal of microbial contamination from soil to crops [22,28].…”
Section: Introductionmentioning
confidence: 99%